Molecular Epidemiology and Colistin Resistant Mechanism of mcr-Positive and mcr-Negative Clinical Isolated Escherichia coli - Luo, Qixia; Yu, Wei; Zhou, Kai; Guo, Lihua; Shen, Ping; Lu, Haifeng; Huang, Chen; Xu, Hao; Xu, Shaoyan; Xiao, Yonghong; Li, Lanjuan (Frontiers in Microbiology, 2017)
Transmissible colistin resistance mediated by the mcr gene has been reported worldwide, but clinical isolates of mcr-negative colistin-resistant Escherichia coli are rarely reported. The aim of this study was to evaluate the mechanism of colistin resistance among mcr-positive and mcr-negative E. coli clinical isolates by performing a molecular epidemiological surveillance. For the first time ever, we show nearly the same isolation ratio for mcr-negative and mcr-positive colistin-resistant clinical isolates (47.5% and 52.5%, respectively), with no demonstrable nosocomial transmission. We provide evidence for the prevalence of the mcr-positive IncX4 plasmid and its high potential for horizontal transfer, with no obvious sequence type (ST) preference. In addition, the minimal inhibitory concentrations (MICs) of colistin of the mcr-negative E. coli isolates were obviously higher than those of mcr-positive isolates. Apart from the usually detected genes, i.e. pmrAB, phoPQ, and mgrB, other genes may be associated with the colistin resistance in mcr-negative E. coli. To the best of our knowledge, this is the first paper to report the molecular epidemiological surveillance and the proper mechanism of colistin resistance in mcr-negative E. coli clinical isolates. Together, the results show that colistin resistance was prevalent not only in the mcr-positive clinical E. coli isolates but also in the mcr-negative isolates.